Théologie du désordre. Islam, ordre et désordre au Sahara - Abdel Wedoud Ould Cheikh (L’Année du Maghreb)
This contribution deals with some aspects of the interrelations between (dis)order and (il)legality in the Sahara, in light of the debates and positions informing the thoughts and writings of the Moorish fuqahâ’ confronted with the lack of a fully legitimate power, from an Islamic viewpoint, in the pre-colonial Western Sahara. Some of these theologians declared themselves in favour of a jihâd aiming at the coming of such a power; others, to the contrary, firmly opposed this idea. Turning back to this old controversy helps to show the historicity of the problem of the jihâd which arose recently in the Saharan areas, in close connection with a noticed growth of insecurity in these mentioned areas, associated with all kinds of illegal activities (kidnappings, assassinations, diverse trafficking, etc.), sometimes legitimized by jihâdist motives.